Engineering cytochrome P450BM3 into a drug metabolising enzyme - Yorke, J (2012)
Directed evolution studies by Whitehouse et al. identified several variants of P450BM3 (CYP102A1) with enhanced substrate oxidation rates across a range of substrates. This thesis describes the use of these ‘generic accelerator’ variants, in combination with selectivity altering mutations to engineer P450BM3¬ for the oxidation of pharmaceuticals. Using engineered variants the non-steroidal anti-inflammatory drug diclofenac was metabolised to the primary human metabolites 4′- and 5-hydroxydiclofenac, with total conversion of 2 mM substrate by 5 μM enzyme. The local-anaesthetic lidocaine and the steroid testosterone were similarly metabolised to human metabolites. This is the first report of a drug compound being totally converted to the human metabolites by a P450BM3 variant, and is also the first report of lidocaine metabolism by a P450¬BM3 variant. The engineered variants are akin to CYP3A4, the primary human drug metabolising enzyme, as they show activity towards a range of compounds including anionic, cationic and neutral drugs. This range of activity is at the expense of NADPH coupling, which remains low with these substrates. In order to more fully understand the origin of the rate enhancing properties of the generic accelerator variants, spectroelectrochemical, stopped-flow and kinetic studies were performed. A custom optically transparent thin layer electrode system was designed and fabricated for use in spectroelectrochemical titrations. A spectroelectrochemical cell and gold mesh electrode were designed and used in spectroelectrochemical investigations of P450BM3 variants, as well as other P450s and their redox partners. These spectroelectrochemical, stopped-flow and kinetic studies, in combination with X-ray crystal structures provided insight into the origin of the rate enhancing properties of these enzymes and supplied the first example of the complete characterization of the thermodynamic and kinetic properties of WT and mutant P450BM3 for the oxidation of a non-natural substrate. The generic accelerator variants are, in the resting state, in a more catalytically ready conformation than the WT enzyme, and reorganization energy barriers appear to be lowered, so that fewer substrate-induced structural changes are required to promote electron transfer and initiate the catalytic cycle.